Comparative Effectiveness of Aspirin Dosing in Cardiovascular Disease - Jones, W. Schuyler; Mulder, Hillary; Wruck, Lisa M; Pencina, Michael J; Kripalani, Sunil; Muñoz, Daniel; Crenshaw, David L; Effron, Mark B; Re, Richard N; Gupta, Kamal; Anderson, R. David; Pepine, Carl J; et al. (The New England journal of medicine, 2021)
In an open-label, pragmatic trial, patients with cardiovascular disease were randomly assigned to a strategy of 81 mg or 325 mg of aspirin daily. A substantial proportion of those assigned to the 325-mg dose switched to the 81-mg dose, and there were no significant differences in cardiovascular events or major bleeding between the two groups.